2010
DOI: 10.1007/s12024-010-9205-6
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic subarachnoid hemorrhage and the COL3A1 gene: emergence of a potential causal link

Abstract: We describe two previously unreported associations in four cases. The first two cases demonstrate an association between segmental mediolytic arteriopathy and vascular Ehlers-Danlos syndrome. The second two cases illustrate an association between vascular Ehlers-Danlos syndrome and traumatic subarachnoid hemorrhage. In case 1, there was acute subarachnoid hemorrhage and mesenteric artery dissection. In case 2, there was an acute mesenteric artery dissection with intestinal infarction. In both cases 1 and 2, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…The COL3A1 p.Lys1313Arg variant detected in ID 655 has been previously reported in two unrelated patients with vascular EDS. [18] However, collagen microscopy and biochemistry were normal in the patient, neither the patient nor her sister, who also carried the variant, had features of vascular EDS and structural studies indicated that the variant was unlikely to impair C-propeptide-mediated helical winding. [29,30] Consistent with previous reports, we observed significant phenotypic overlap between our EDS diagnostic categories and other HDCT as well as overlap amongst patients with pathogenic variants in individual causative genes.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The COL3A1 p.Lys1313Arg variant detected in ID 655 has been previously reported in two unrelated patients with vascular EDS. [18] However, collagen microscopy and biochemistry were normal in the patient, neither the patient nor her sister, who also carried the variant, had features of vascular EDS and structural studies indicated that the variant was unlikely to impair C-propeptide-mediated helical winding. [29,30] Consistent with previous reports, we observed significant phenotypic overlap between our EDS diagnostic categories and other HDCT as well as overlap amongst patients with pathogenic variants in individual causative genes.…”
Section: Discussionmentioning
confidence: 85%
“…One of these patients (ID 893) carried a helical domain Arg>Cys variant in COL1A1, a number of which have been shown to be pathogenic in previous reports. [23] Although two particular variants had previously been reported as pathogenic, we classified these as VUS's in our patients (Table 4 & S5): a COL1A2 variant [17] (ID 629) due to nonsegregation in first degree relatives and COL3A1 C-propeptide variant [18] (ID 655) because of lack of clinical or biochemical corroboration in the index case or her first-degree relative who also carried the variant. Two hypermobility EDS patients were each found to have two separate VUS's: ID 38 in COL3A1 and COL5A2; ID 39 in COL1A2 and COL3A1 (Table 4; and Table S4).…”
Section: Ngsmentioning
confidence: 99%
“…Several heritable connective tissue disorders have also been shown increase the risk of SAH [22][23][24]. It has been suggested that ''vascular Ehlers-Danlos syndrome may be related to the pathogenesis of traumatic vertebral artery injury, in some cases'' [22].…”
Section: Discussionmentioning
confidence: 99%
“…Differential diagnosis of SAH in children are listed by Nguyen et al; infections (malaria and hepatitis), intravascular coagulopathy, malignacies (for instance leukemia), clotting disorders, liver diseases, gastrointestinal malabsorption diseases, metabolic disorders, enzyme defect disorders [3]. Pickup and Pollanen add connective tissue disorders like Ehlers-Danlos syndrome to the list [27], and Reece and Sege child abuse and accident [2].…”
Section: Discussionmentioning
confidence: 99%